2015
DOI: 10.3233/jpn-2012-0556
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of caring for children with cerebral palsy on the family in a developing country

Abstract: Having a child with cerebral palsy (CP) in developing countries of the world is particularly burdensome. This study investigated psychosocial impact on the family caring for a child with CP, examined possible association of severity of gross motor function impairment on the psychosocial impact and compared impact scores of families with CP child with that of families with no CP child. Participants consisted of 117 parents/caregivers of children with CP and 117 parents/caregivers of children without CP whose ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Levels of parental stress were associated with a child's level of gross motor function capacity (Davis et al, 2009; Palisano et al, 2009; Schuengel et al, 2009; Sipal et al, 2009; Fiss et al, 2013), whether or not the child had an intellectual disability (Buran et al, 2008; Palisano et al, 2009; Vargus-Adams, 2011; Pfeifer et al, 2013), the level of communication impairment (Buran et al, 2008; Almassri et al, 2011; Vargus-Adams, 2011), and the level of physical pain associated with the CP diagnosis (Sipal et al, 2009; Vargus-Adams, 2011). Interestingly, research by Davis and colleagues (2009) and later in studies by Ogwumike, Adeniyi and Obidiegwu (2012), Fiss et al (2013) and Pfeifer et al (2013) found that parents of children diagnosed with CP experience a significant increase in levels of psychological distress that was not influenced by the level of gross motor function capacity of the child. However, five of the studies showed that families who have a child with a more severe diagnosis will require more assistance with home modifications (Palisano et al, 2009; Bourke-Taylor, Cotter & Stephan, 2013), transportation (Almassri et al, 2011; Bourke-Taylor et al, 2013)), financial assistance (Buran et al, 2008; Davis et al, 2009; Almassri et al, 2011), and access to services and recreational activities for their child (Buran et al, 2008, Almassri et al, 2011; Bourke-Taylor et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Levels of parental stress were associated with a child's level of gross motor function capacity (Davis et al, 2009; Palisano et al, 2009; Schuengel et al, 2009; Sipal et al, 2009; Fiss et al, 2013), whether or not the child had an intellectual disability (Buran et al, 2008; Palisano et al, 2009; Vargus-Adams, 2011; Pfeifer et al, 2013), the level of communication impairment (Buran et al, 2008; Almassri et al, 2011; Vargus-Adams, 2011), and the level of physical pain associated with the CP diagnosis (Sipal et al, 2009; Vargus-Adams, 2011). Interestingly, research by Davis and colleagues (2009) and later in studies by Ogwumike, Adeniyi and Obidiegwu (2012), Fiss et al (2013) and Pfeifer et al (2013) found that parents of children diagnosed with CP experience a significant increase in levels of psychological distress that was not influenced by the level of gross motor function capacity of the child. However, five of the studies showed that families who have a child with a more severe diagnosis will require more assistance with home modifications (Palisano et al, 2009; Bourke-Taylor, Cotter & Stephan, 2013), transportation (Almassri et al, 2011; Bourke-Taylor et al, 2013)), financial assistance (Buran et al, 2008; Davis et al, 2009; Almassri et al, 2011), and access to services and recreational activities for their child (Buran et al, 2008, Almassri et al, 2011; Bourke-Taylor et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Parents nurturing a child with CP often experience isolation, anxiety, and depression. 14,15 Therefore, meeting the informational, resources, emotional, social, and monetary needs of the caregiver would be crucial to reduce their burden. 16,17 Moreover, since children with CP require long-term multidisciplinary care, providing a continuum of care through a family-centered approach may be able to reduce the caregiver burden, enhance their capacities and empower them to care for their children.…”
Section: Introductionmentioning
confidence: 99%